Future of 3D printing: How 3D bioprinting technology can revolutionize healthcare?. Issue 13 (19th June 2018) - Morris, Steven
Abstract : Currently there are more than 2, 000 children on the transplant waiting list—and more than 100, 000 Americans nationwide—awaiting a matching organ. Most children aged one through 10 are awaiting a kidney, liver, or heart. As with any transplant, there are two ways to find an organ—someone can donate or someone can die. Unfortunately, the supply falls far short of the demand, leaving people to die every day waiting for a second chance at life. Scientific and medical experts, however, continue to develop promising technology like 3D bioprinting that could save thousands of lives without the need of a donor.